2020
DOI: 10.1111/aor.13816
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of heart transplantation in patients bridged with Impella 5.0: Comparison with native chest transplanted patients without preoperative mechanical circulatory support

Abstract: The Impella (Abiomed, Danvers, MA, USA) has become an important adjunct treatment modality in bridging patients with end‐stage heart failure to recovery or orthotopic heart transplantation (HTx). We compared the outcome of patients directly bridged to HTx with the Impella 5.0 versus patients without mechanical circulatory support (MCS). Patients with no previous sternotomy or MCS, who were transplanted between September 2014 and March 2019 were included in this retrospective analysis. Impella 5.0 was implanted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
(44 reference statements)
2
7
0
Order By: Relevance
“…Similar improvements have been reported with the use of other temporary MCS devices, with better survival outcomes post-HTx in the current era compared to previous time periods [21]. For candidates who were supported with the Impella 5.0 (Abiomed, Danvers, MA, USA), survival at 6 months post-HTx is reportedly similar to recipients who were not on MCS devices [22].…”
Section: New Allocation Systemsupporting
confidence: 69%
“…Similar improvements have been reported with the use of other temporary MCS devices, with better survival outcomes post-HTx in the current era compared to previous time periods [21]. For candidates who were supported with the Impella 5.0 (Abiomed, Danvers, MA, USA), survival at 6 months post-HTx is reportedly similar to recipients who were not on MCS devices [22].…”
Section: New Allocation Systemsupporting
confidence: 69%
“…Despite these differences in donor and recipient characteristics, we found no significant difference in 1‐year survival between the two cohorts. Other studies present similar results, with no difference in 30‐day, 6‐month, or 1‐year post‐transplant survival 18,19 . This is in contrast to the pre‐allocation analysis of patients bridged with temporary MCS from the International Society of Heart and Lung Transplantation registry between 2005 and 2016, which found increased post‐transplant mortality in percutaneous temporary LVADs ( n = 75, hazard ratio 1.83, 95% CI 1.09–3.08) compared to durable LVADs 20 .…”
Section: Discussionmentioning
confidence: 57%
“…While the literature on Impella remains limited, Impella 5.0 has been studied in the context of BTT. Patients in cardiogenic shock who underwent BTT with Impella 5.0 have been shown to have good outcomes and comparable short‐term survival as those bridged without MCS 3,19 . Furthermore, Seese et al.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] One recent study demonstrated that the Impella 5.0 percutaneous axial flow device reduced serum creatinine levels within 24-h of implantation. 25 Bridging with intra-aortic balloon pump (IABP) has been shown to decrease serum creatinine in multiple studies as well. [26][27][28] This analysis evaluated whether these and other forms of temporary MCS were associated with changes in the CKD stage in patients awaiting a heart transplant.…”
Section: Discussionmentioning
confidence: 99%